The interaction between problematic internet use, diet quality, and disordered eating risk in adolescents: a mediation and network analysis - Mevra Aydin Cil; Sumeyye Carikci; Elham Foroudi Pourdeh; Haitham Jahrami (Eating and Weight Disorders)
Abstract Background Adolescence is a key period for problematic internet use (PIU) and disordered eating (DE), with prior studies linking them, but the role of diet quality unclear. Objective This study aimed to investigate the relationships between PIU, diet quality, and DE in adolescents using mediator and network analyses, with a specific focus on the mediating role of diet quality. Methods A cross-sectional study was conducted with 647 high-school students in Erzurum, Turkey. Data were collected through validated instruments, including the Young Internet Addiction Test, Social Media Addiction Scale, KIDMED Mediterranean Diet Quality Index, and Eating Attitudes Test (EAT-26). Statistical analyses included mediation modeling and network analysis (NA). Results The prevalence of DE risk was 18.2%, while 27% of participants met the criteria for social media addiction. Additionally, 3.6% were classified as at potential risk for internet addiction. In addition to PIU and social media addiction, higher maternal education levels were also significantly associated with greater DE risk (p < 0.05). Mediation analysis showed that problematic internet use was linked to lower adherence to the Mediterranean diet (β = −0.12, p = 0.002), which was associated with higher DE risk (β = 0.15, p < 0.001). The indirect effect was significant (β = −0.02, p = 0.016), supporting partial mediation. NA identified internet addiction as the central node, linking DE risk, social media disorder, and diet quality. Conclusion Internet addiction is linked to increased DE risk, mediated by diet quality, highlighting the need to address it in adolescent interventions. Longitudinal studies are needed. Level Evidence V Evidence obtained from a cross-sectional descriptive study.